Undrained shear behavior of silty sand with a constant state parameter considering initial stress anisotropy effect - Li, Peipei; Zhu, Chen; Pan, Xiaodong; Lv, Bin; Pan, Kun (Scientific reports, 2024)
Field observations in sedimentation and erosion-prone areas indicate that most natural sand deposits may contain a certain amount of non-plastic fines and are often under anisotropic stress conditions. A series of triaxial compression tests were performed on clean and silty sand with fines content f c ranging from 0 to 20% at an initial mean effective stress of p 0 ′ = 100 kPa and varying consolidation conditions to understand the impact of initial stress anisotropy on undrained shear behavior. The results indicate that the state parameter ψ is a superior predictor for characterizing the responses of sand-fines mixtures compared to the global void ratio and relative density. A comparison of the behavior of clean and silty sand with a constant ψ (= − 0.03) confirms that the sample with 10% f c exhibits the strongest dilation and greatest shear resistance, irrespective of the consolidation conditions. It is also demonstrated that the initial stress anisotropy with a comparably higher static stress ratio η s typically diminishes the shear strength of mixtures. However, the influence of initial stress anisotropy on soil stiffness is not unilateral. The sample consolidated to a negative η s is stiffer than that under isotropic consolidation, while the presence of a positive η s leads to a decrease in the secant Young ' s modulus.